A randomised controlled feasibility trial of Group Cognitive Behavioural Therapy for people with severe asthma. (28th May 2017) - Yorke, Janelle; Adair, Pauline; Doyle, Anne-Marie; Dubrow-Marshall, Linda; Fleming, Sharon; Holmes, Leanne; Menzies-Gow, Andrew; Niven, Rob; Pilling, Mark; Shuldham, Caroline
ABSTRACT: Objectives : Evidence for the efficacy of Cognitive Behavioural Therapy (CBT) in asthma is developing but it is not known if this translates to benefits in severe asthma or if a group approach is acceptable to this patient group. This study aimed to assess the feasibility and acceptability of Group-CBT in severe asthma. Method : This was a two-centre, randomised controlled parallel group feasibility study. Eligible participants (patients with severe asthma and a clinically significant diagnosis of anxiety and/or depression – Hospital Anxiety and Depression Scale (HAD) score greater than 8 for the anxiety or depression sub-scale) received Group-CBT in weekly sessions for eight consecutive weeks and usual care or usual care only. Follow-up was for 16 weeks and end points were: Asthma Quality of Life Questionnaire, Asthma Control Questionnaire, HAD, Dyspnoea-12, EuroQual-5D and EuroQuol-VAS. Results : 51 patients were randomised: 36% (51 out of 140) consent rate and attrition at week 16 was 12. Screening logs indicated that study take-up was influenced by patients living long distances from the treatment centre and inability to commit to the weekly demands of the programme. Drop-out was higher in Group-CBT compared due to inability to commit to the weekly programme because of poor health. Participants who contributed to focus group discussions reported that Group-CBT contributed to a better understanding of their illness and related approaches to anxiety management and acceptance of their asthma condition. Although weekly face-to-face sessions were challenging, this was the preferred method of delivery for these participants. Conclusions : This feasibility study shows that Group-CBT warrants further investigation as a potentially promising treatment option for patients with severe asthma. It has been possible but not easy to recruit and retain the sample. Options for a less demanding intervention schedule, such as less frequent face-to-face visits and the use of web-based interventions, require careful consideration.